2019
DOI: 10.1038/s41598-019-47177-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties of 5Z-(4-fluorobenzylidene)-2-(4-hydroxyphenylamino)-thiazol-4-one

Abstract: 4-thiazolidinones, which are privileged structures in medicinal chemistry, comprise the well-known class of heterocycles and are a source of new drug-like compounds. Undoubtedly, the 5-bulky-substituted-2,4-thiazolidinediones - a class of antihyperglycemic glitazones, which are peroxisome proliferator-activated receptor gamma (PPARγ) agonists, are the most described group among them. As there are various chemically distinct 4-thiazolidinones, different subtypes have been selected for studies; however, their ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 60 publications
6
18
0
Order By: Relevance
“…To date, thiazolidinone-based compounds have been shown to initiate the apoptotic process in various cancerous cell lines (Szychowski et al 2017a , b , 2019 ). Caspase-3 activity assay was performed to measure the effects of Les-2194, Les-3640, Les-5935, and Les-6166 on the apoptotic process in the 3T3-L1 cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, thiazolidinone-based compounds have been shown to initiate the apoptotic process in various cancerous cell lines (Szychowski et al 2017a , b , 2019 ). Caspase-3 activity assay was performed to measure the effects of Les-2194, Les-3640, Les-5935, and Les-6166 on the apoptotic process in the 3T3-L1 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has demonstrated that 4-thiazolidinone-based derivatives (thiopyrano[2,3- d ]thiazole derivative Les-2194 and thiazolidinone-pyrazoline hybrid molecule Les-3640) cause apoptotic cell death in human squamous carcinoma cells (SCC-15) with key involvement of PPARγ (Szychowski et al 2017a , b ). Moreover, another compound studied by our team 5 Z -(4-fluorobenzylidene)-2-(4-hydroxyphenylamino)-thiazol-4-one (Les-236) has been found to exhibit broad cytotoxic and proapoptotic action in SCC-15, lung carcinoma (A549), colon adenocarcinoma (CACO-2), neuroblastoma (SH-SY5Y), and skin fibroblast (BJ) cell lines (Szychowski et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the classes of heterocycles with promising anticancer activity is the series of 4-thiazolidinone (4-TZD) derivatives. To date, it has been described that various 4-thiazolidinones exhibit anticancer properties demonstrated in numerous in vitro and in vivo models [ 10 , 12 , 13 , 14 , 18 , 25 , 26 , 27 , 28 ]. The determination of the impact of xenobiotics on metabolic activity is one of the most relevant analyses allowing the formulation of preliminary assumptions about their application potential.…”
Section: Discussionmentioning
confidence: 99%
“…They were found to act mainly in a PPARγ-dependent manner [ 25 , 26 ]. A similar effect was produced by the action of 5 Z -(4-fluorobenzylidene)-2-(4-hydroxyphenylamino)-thiazol-4-one (Les-236), e.g., in lung carcinoma (A549) and colon adenocarcinoma (CACO-2) cell lines and in normal skin fibroblasts (BJ) [ 27 ]. However, 4-TZD-based compounds are also able to have a negative influence on healthy cells, such as mouse preadipocytes (3T3-L1 cell line), although this effect is observed only at high micromolar concentrations (100 µM of Les-2194 and Les-3640) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dipolar cycloaddition is a preferable route for synthesis of thiazolidinones, isoxazoles and isoxazolines [9]. 1,3-Dipolar or [3+2] cycloaddition is a reaction between a molecule containing a  bond ( an alkene, alkyne, etc) known as 1,3 dipolarophile with a highly polarized ionic compound called a 1,3 dipole.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 99%